Luciferase reporter cells as a platform to detect SMAD-dependent collagen production - Lohcharoenkal, Warangkana (J Biosci Bioeng, 2014)
Aberrant collagen production can lead to many diseases such as fibrosis. Current methods of collagen detection are insensitive, time consuming and laborious. We have developed a rapid, sensitive assay using chemiluminescence-based reporter cell system. Stable 3T3/NIH-SMAD-luciferase cells were generated for detection of collagen expression through TGF-β signaling, a major fibrogenic pathway. We demonstrated that these reporter cells could be used as a rapid screening tool for detection of SMAD-dependent collagen production with higher sensitivity than existing assays. Flexibility of this cell-based assay in different detection platforms makes it attractive for high throughput screening of potential fibrogenic agents and drug candidates.